Renal Cancer Current Status and Innovations - Anderson, Christopher; Afshar, Mehran; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Renal Cancer: Current Status and Innovations provides a useful guide to the fundamental basics and latest diagnostic and treatment techniques for Renal Cancer. It features clearly structured and easy-to-understand chapters enabling the reader to develop a thorough understanding of screening, surveillance, diagnostics, pathology, robotic and open surgical approaches, ablation, medical treatment, psychology, and future innovations. The book provides a valuable resource for the full spectrum of clinicians involved in the multidisciplinary management of Renal Cancer.
Introduction to the Multidisciplinary approach to Renal Cancer -- Imaging in Renal Cancer -- Application of Simulation Techniques -- Cognitive Simulation & Non technical skills training -- Team training -- Active surveillance and Percutaneous Treatment -- Endoscopic Surgery -- Laparoscopic Renal Surgery -- Robotic Surgery -- Focal Therapies -- Pre and Post-surgery, treatments -- Big Data and Renal Outcomes -- Future perspectives. .
Keywords: Surgery; Internal medicine; Urology; Surgery; Internal Medicine; Internal Medicine; Urology; Kidney Neoplasms